The Influence of Product Quality, Price Perception, Place and Promotion on Interest in Buying Food and Beverage at Tamelo Atap Resto - Muhammad Fakhri Athallah; Beureukat Beureukat; Adam Nurkholik; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
Study This own objective as knowledge And analyze the influence of product quality, price perception, place and promotion on interest in buying food and beverages in Tamelo Rooftop Resto. Type The research uses quantitative descriptions and inferential analysis using primary data in the form of closed questionnaires to 100 respondents, namely interest in buying food and beverage at Tamelo Atap Resto, and the data analyzed use analysis Regression Linear Multiple. And data data which has been fulfilled by test validity, test reliability, test assumption classic and test appropriateness model, and the regression equation is obtained.